Psidium guajava: A review on its potential as an adjunct in treating periodontal disease - Ravi, K; Divyashree, P (Pharmacognosy Reviews)
Plants for thousands of years have been used to enhance health and for medicinal purposes. Psidium guajava is one which has an enormous wealth of medicinal value. It for long has been known for its anti‑inflammatory, antimicrobial, antioxidant, antidiarrheal, antimutagenic properties. Despite of its widespread biologic uses there is a dearth of information on its therapeutic effect in the treatment of periodontal disease. Hence, this review is an attempt to highlight the potential of P. guajava in the treatment of periodontal disease. Internet databases PubMed, Google Scholar were searched and the most relevant articles were considered for review.
Keywords: Antiplaque; gingivitis; guaijaverin; periodontitis; Psidium guajava; quercetin